The New Testament : the history of the investigation of its problems - Kümmel, Werner Georg, 1905-1995 (Abingdon Press, 1972)
"There can be nothing but praise for the treatment of the subject from the turn of the seventeenth to the eighteenth century up to the present day. Kummel finds the decisive stimuli of New Testament research as we now understand it in Textual Criticism and, interestingly enough, in English Deism. He goes on to trace scientific study from Semler and Michaelis up to the consistently historical approach inaugurated by D. B. Strauss and F. C. Baur. The other major developments are grouped under the main headings of 'The History of Religion School' and the 'HistoricoTheological View'. On this broad canvas the detail is superbly organized. Perhaps the outstanding feature of the book is the large amount of illustrative material taken from the writings of the principal scholars whose views are adumbrated and criticized. Behind the selection of material lie great skill and perception. To draw attention to the rich vein of source material is in no way to depreciate Kummel's own contribution which sets in context and gives significance to the excerpts. He makes the reader aware of what precisely are the problems of interpretation, how and why they arise when they do, how they are dealt with by this scholar and that, what is the strength and the weakness of each approach and hypothesis. Running commentary and illustrative material are both enhanced by over five hundred comprehensive notes, full indices, and bibliography. Here is an instrument of study for which we have long been looking and can only receive with gratitude" -- Marcus Ward in The Heythrop Journal.